Qur'an Studies and Islamic Education A Critical Pedagogic Perspective: An Analysis of Contemporary Interpretation - Guntur Hasby (Journal Research of Social Science, Economics, and Management, 2025)
This article explores the conceptual relationship between Islamic education and critical pedagogy, two intellectual traditions that share the same emancipatory mission: to liberate human beings from ignorance, oppression, and moral alienation. Drawing upon a literature-based analysis of the works of Paulo Freire, Farid Esack, Fazlur Rahman, and Syed Muhammad Naquib al-Attas, this study reveals that both traditions converge in a Islamic education–critical paradigm a framework of education that integrates spiritual consciousness, moral responsibility, and social justice. The study argues that critical pedagogy enriches the practical dimension of Islamic education by emphasizing dialogical learning, participatory reflection, and critical awareness, while Islamic epistemology provides a theological foundation for ethics, purpose, and transcendence within educational practice. In this synthesis, education becomes not merely a transfer of knowledge, but a praxis of liberation that combines ‘ilm (knowledge), ‘amal (action), and ‘adl (justice) under the unity of tawhid. Ultimately, this research concludes that Islamic education grounded in critical pedagogy can cultivate learners who are both spiritually conscious and socially transformative individuals who seek the divine through justice and the human through faith.